Isolation of saprophytic Leptospira spp. from a selected environmental water source of Argentina = Aislamiento de Leptospira spp. saprófitas desde fuentes de agua en un ambiente seleccionado de Argentina - Scialfa, Exequiel; Grune Loffler, Sylvia; Brihuega, Bibiana Felicitas; Aguirre, Pablo; Rivero, Marina (2018)
Ten Leptospira spp. strains were isolated from water samples from Nievas stream, Olavarría, Buenos Aires province (Argentina). The isolates showed the typical motility and morphology of the genus Leptospira under dark field microscopy, developing in liquid EMJH medium after eight days of incubation at 13 °C and 30 °C. All isolates were negative by the Multiple Locus Variable Number Tandem Repeat Analysis (MLVA). Molecular identification by 16S rRNA gene sequencing identified all isolates as nonpathogenic leptospires. Four isolates showed a genetic profile identical to that of the reference strain Leptospira biflexa serovar Patoc, and six isolates revealed sequence similarities within the 97–98% range, closely related to Leptospira yanagawae and Leptospira meyeri, respectively. Strains ScialfaASA42, ScialfaASA45, ScialfaASA44, ScialfaASA47, ScialfaASA49, ScialfaASA50 and ScialfaASA51 possibly represent a novel species of the genus Leptospira.